FLYPAPER EFFECT DANA ALOKASI UMUM (DAU)DAN PENDAPATAN ASLI DAERAH (PAD) TERHADAP BELANJA DAERAH DI KOTA PAREPARE - KS, Ishak; Arafah, Rudy; M, Hasnah (Economos : Jurnal Ekonomi dan Bisnis, 2019)
Unconditional grants that are proxied by the General Allocation Fund are determined based on the fiscal space, namely the fiscal needs minus the regional fiscal capacity and the basic allocation allocated as a lump (lump sum) from the central government. This study aims to determine the Flypaper Effect on General Allocation Fund (GAF) and Local Own Source Revenue (LOSR) towards regional expenditure of Parepare City. This research uses descriptive method, the research is conducted to find out the value of the independent variable, either one or more variables (independent) without making comparisons, or connecting with other variables.To find out the value of variables without making comparisons or connecting with other variables, where the variables in the study are regional income sourced from regional expenditure based on GAF and LOSR. The results showed that the Flypaper Effect occurred in the General Allocation Fund and Local Own-Source Revenue toward Regional Expenditure in the Regional Government of Parepare City in the 2014-2018 period. The Flypaper Effect occurs because in this case the General Allocation Fund is used first for Regional Expenditure rather than Local Own-Source Revenue.